The Use of NotebookLm Media to Strengthen Early Childhood Religious Moderation at Tpq Al-Irsyad Saturday Week, Bengkulu City - Nabila Gustina; Desy Eka Citra Dewi; Moza Thania Salsabella Putri; Widya Lestari; Melin Maharani; Abibtrin (Edumaspul: Jurnal Pendidikan, 2026)
Internalization of religious moderation values for early childhood at TPQ Al Irsyad Pekan Sabtu, Bengkulu City, has faced methodological constraints in the form of conventional verbalistic lectures and static text, triggering student boredom and low retention of tolerance values. This Thematic Community Service (KKN) activity based on Research by the PGMI Study Program Group 12 aims to transform the conventional learning model by utilizing the NotebookLM AI platform as a medium for synthesizing, structuring teaching material summaries, and adaptive instructional audio sources for moderation values. The implementation method uses the Asset-Based Community Development (ABCD) approach which includes the stages of Discovery, Dream, Design, and Destiny. The results show a significant increase in educators' technological literacy in managing religious moderation data sources, visual and material quality of character teaching materials, and student interaction. Measurement using the Societal Impact Index (SII) confirmed a partner satisfaction level of 92.6% (very high). The resulting social impacts include the growth of a moderate digital religious ecosystem, increased student inclusivity attention, and institutional independence in technology-based learning in Pekan Sabtu, Bengkulu City